Assisted reproductive techniques and NaProTechnology - Dowbór-Dzwonka, Aneta; Cegła, Bernadeta; Filanowicz, Małgorzata; Szymkiewicz, Ewa (Polish Journal of Public Health, 2012)
Infertility is a significant and constantly increasing individual and social problem. It is estimated that at present it affects approx. 15 to 20 percent of couples. Inability to conceive a child elicits a range of unfavourable implications in the scope of emotional experiences, in the partner’s relationship and in a broader social perspective.Making a decision on undergoing diagnostics and infertility treatment is a difficult and often postponed moment for many couples. This is an expression of the escape model of dealing with a situation that threatens with a fall of self-esteem. However, if a couple reacts in a task-oriented way and participates in the diagnostic and therapeutic procedure, new doubts appear connected with the medical, psychological, social and ethical sphere. Infertility treatment sometimes prompts fear connected with the stripping of intimacy, loss of control over one’s body, possible complications and unsuccessful therapy.This article is an analysis of the medical and the other aspects of struggling with infertility with reference to two extremely different methods of solving this problem: NaProTechnology as a process of assisting natural procreation and assisted reproductive techniques with a special consideration of in vitro fertilization.